Organo-mineral interactions in contrasting soils under natural vegetation - Jones, Edward; Singh, Balwant (Frontiers in Environmental Science, 2014)
Organo-mineral interactions are important for the cycling and preservation of organic carbon (OC) in soils. To understand the role of soil mineral surfaces in organo-mineral interactions, we used a sequential density fractionation procedure to isolate < 1.6, 1.6-1.8, 1.8-2.0, 2.0-2.2, 2.2-2.6 and >2.6 g cm-3 density fractions from topsoils (0-10 cm) of contrasting mineralogies. These soils were under natural vegetation of four major Australian soil types - Chromosol, Ferrosol, Sodosol and Vertosol. The soils and their organic matter (OM) contents were found to be partitioned in four distinct pools: i) particulate organic matter < 1.6 g cm-3; ii) phyllosilicate dominant 1.8-2.2 g cm-3; iii) quartz and feldspar dominant >2.6 g cm-3; and iv) Fe oxides dominant >2.0 g cm-3 (in the Ferrosol.) X-ray photoelectron spectroscopy was used to investigate organic C and N bonding environments associated within each density fraction. Mineral pools were shown to be enriched in distinct organic functional groups: phyllosilicate dominant fractions were enriched with oxidized OC species (C-O, C=O, O-C=O) and protonated amide forms; quartz and feldspar dominated fractions were enriched in aliphatic C and protonated amide forms; Fe oxides dominant fractions had the greatest proportions of oxidized OC species and were low in protonated amide forms. The enrichment of different C species was related to the interaction of functional groups with the mineral surfaces. These results demonstrate the potential of mineral surfaces in influencing the chemical composition of OM bound in surfaces reactions and subsequently the stability of OM in organo-mineral interactions.